Antibiotic usage pattern among under-five wheezers: A Bhubaneswar based study - Panda, Jyochnamayi; Mishra, Jyotiprakash (Indian Journal of Child Health, 2018)
Introduction: Acute under-five wheezers are the most suitable group for targeting focus aimed at reducing unnecessary use of antibiotics. Viral bronchiolitis is an important cause of wheezing in under-five children. Rationality behind antibiotic usage has rarely been reported from Odisha. Aim: The aim of the present study is to look into the decision of private practitioners of Bhubaneswar, Odisha, for an antibiotic prescription to under-five wheezers. Materials and Methods: Hundred prescriptions of private practitioners for under-five patients suffering from acute wheeze were analyzed between January and June 2016. The prescriptions were grouped as with antibiotics (Group A) and without antibiotics (Group B). The groups were compared for the presence of clinical, hematological, and radiological signs and results were statistically analyzed. Result: The number of prescriptions with antibiotic inclusion is higher (67%). Antibiotics are mostly prescribed to younger patients. Antibiotic administration was significantly higher with the symptoms of fever, tachypnea, crepitation’s and leukocytosis, and X-ray findings. (p<0.05) The average recovery period was almost the same in both the groups. The prescription patterns in the present study show rational usage.